Perceptions of the organizational climate by informal groups in two public elementary schools - Calip, Jeremia de Vera 1948- (1973)
This study determined to know whether perceptions about the existing and desired organizational climates of Sto. Nino and Concepcion I, in the Third District of Marikina Rizal, held by members of an informal group are more similar among the members than the perceptions of the organizational climate held by the total membership. Data gathered through a sociometric instrument and a questionnaire were analyzed using variance and critical ratio. No differences were found between the informal group's and the total membership's perceptions.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Teachers -- Marikina, Rizal; Perception -- Case studies